State variation in HIV/AIDS health outcomes: the effect of spending on social services and public health. - Talbert-Slagle, Kristina M; Canavan, Maureen E; Rogan, Erika M; Curry, Leslie C; Bradley, Elizabeth H (AIDS (London, England), 2015)
Despite considerable advances in the prevention and treatment of HIV/AIDS, the burden of new infections of HIV and AIDS varies substantially across the country. Previous studies have demonstrated associations between increased health care spending and better HIV/AIDS outcomes; however, less is known about the association between spending on social services and public health spending and HIV/AIDS outcomes. We sought to examine the association between state-level spending on social services and public health and HIV/AIDS case rates and AIDS deaths across the U.S.